IMPLEMENTATION OF HUMANISTIC-BASED LEARNING IN STRENGTHENING LITERACY AND NUMERATION IN PRIMARY SCHOOLS - MILLAH NAHDAH HUSNA (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to describe the application of a humanistic approach to learning to improve elementary school students' literacy and numeracy skills. The study used a descriptive qualitative method with data collection techniques through interviews, observations, documentation, and tests on 25 students in grade 3A of Daarul Muttaqien Integrated Islamic Elementary School, Surabaya. The results showed that the humanistic approach was able to improve students' participation, self-confidence, literacy skills, and numeracy skills. Students became more active in discussions, dared to express their opinions, and were able to relate learning materials to everyday life. Improved literacy was seen from the ability to understand reading, while improved numeracy was seen in the ability to solve contextual problems. Most students achieved good to very good learning outcomes. In addition, students felt the learning process was more enjoyable and meaningful because the material was linked to their real experiences. Thus, the humanistic approach is an effective learning strategy to improve the quality of learning and strengthen literacy and numeracy in elementary schools.